2022
DOI: 10.3390/ijms23147887
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones and Transcriptome Analyses Revealed the Dynamics Involved in Spikelet Abortion and Inflorescence Development in Rice

Abstract: Panicle degeneration, sometimes known as abortion, causes heavy losses in grain yield. However, the mechanism of naturally occurring panicle abortion is still elusive. In a previous study, we characterized a mutant, apical panicle abortion1331 (apa1331), exhibiting abortion in apical spikelets starting from the 6 cm stage of panicle development. In this study, we have quantified the five phytohormones, gibberellins (GA), auxins (IAA), abscisic acid (ABA), cytokinins (CTK), and brassinosteroids (BR), in the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The aims of this study were to gain insights into the differences in the molecular mechanisms between resistant and susceptible varieties to cope with C. cassiicola infection and to identify potentially excellent disease-resistance genes in the resistant variety. It has been reported that starch and soluble sugars [ 55 ], phytohormones [ 56 ], and photosynthetic efficiency [ 57 , 58 ] can be used as important reference indicators of plant phenotypic change. In this study, the changes of leaf spot expansion at different time points were recorded as phenotypic observation.…”
Section: Discussionmentioning
confidence: 99%
“…The aims of this study were to gain insights into the differences in the molecular mechanisms between resistant and susceptible varieties to cope with C. cassiicola infection and to identify potentially excellent disease-resistance genes in the resistant variety. It has been reported that starch and soluble sugars [ 55 ], phytohormones [ 56 ], and photosynthetic efficiency [ 57 , 58 ] can be used as important reference indicators of plant phenotypic change. In this study, the changes of leaf spot expansion at different time points were recorded as phenotypic observation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that genes involved in protein protection, biotic stress responses, oxidative stress, programmed cell death, and metabolism were differentially expressed during heat stress (Kotak et al, 2007). Only limited transcriptome data are available for flowering Chinese cabbage under heat stress relative to Chinese cabbage, maize, rice, and Arabidopsis (Song et al, 2014a;Chen et al, 2017;Fan et al, 2017;Huang et al, 2017;Ali et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Using RNA-seq, researchers can identify the expressed genes, particularly those with low abundance. To date, microarrays and RNA-Seq projects have been undertaken in many species, including rice, Chinese cabbage, maize, cotton, Arabidopsis, and vegetables, to detect genes responsive to heat and cold stress (Grover et al, 2013;Nakashima et al, 2014;Ikram et al, 2020;Song et al, 2021;Ali et al, 2022). For example, in Arabidopsis, nearly 30% of DEGs associated with abiotic stresses were identified, and 2,409 genes were involved in salt, cold, and drought stresses (Kreps et al, 2002).…”
Section: Introductionmentioning
confidence: 99%